Hand Dimensions of Mechanics, Carpenters and Welders in Lagos, Southwestern Nigeria - Thomas Monday Onaivi; Sunday Ayoola Oke (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2020)
This paper presents the research conducted on three tradesmen, the mechanics, carpenters, and welders, to measure and compare the left and right hands' dimensions and evaluate the hand index to understand the measurements. Despite rea's utility, the area's utility research has analyzed these technical personnel's hand characteristics. Compared with manufacturing systems, small businesses and entrepreneurs are loss studied. Still, opportunities abound to recognize, appraise, and explore novel instances associated with new product development with detailed information on their hand measurements. Data was collected from mechanics, carpenters, and welders rating in Lagos, Nigeria. The analysis is divided into hand measurements, finger measurements, hand index of the mechanics, carpenters, and welders. The subjects ranged between 18 and 60 years, and measures were made while the subject stands erect. Vernier caliper and tape rules were made. Data concerning heights, hand's height and width, and other aspects of the hand were collected. It was observed that the carpenters have higher values of the hand length to the right third finger. By comparing the mechanics and welders, the mechanics have higher values throughout the experiment. The subjects' heights for carpenters have the highest values. The right and left-hand dimensions are close for the mechanics. There is a greater deviation for the left and right hand for the welders. The deviation is also observed for the carpenters.